Extracellular Vesicles Enhance Multiple Myeloma Metastatic Dissemination - M. Colombo; Domenica Giannandrea; Elena Lesma; Andrea Basile; Raffaella Chiaramonte (2019)
Extracellular vesicles (EVs) represent a heterogeneous group of membranous structures shed by all kinds of cell types, which are released into the surrounding microenvironment or spread to distant sites through the circulation. Therefore, EVs are key mediators of the communication between tumor cells and the surrounding microenvironment or the distant premetastatic niche due to their ability to transport lipids, transcription factors, mRNAs, non-coding regulatory RNAs, and proteins. Multiple myeloma (MM) is a hematological neoplasm that mostly relies on the bone marrow (BM). The BM represents a highly supportive niche for myeloma establishment and diffusion during the formation of distant bone lesions typical of this disease. This review represents a survey of the most recent evidence published on the role played by EVs in supporting MM cells during the multiple steps of metastasis, including travel and uptake at distant premetastatic niches, MM cell engraftment as micrometastasis, and expansion to macrometastasis thanks to EV-induced angiogenesis, release of angiocrine factors, activation of osteolytic activity, and mesenchymal cell support. Finally, we illustrate the first evidence concerning the dual effect of MM-EVs in promoting both anti-tumor immunity and MM immune escape, and the possible modulation operated by pharmacological treatments.